Potential Therapeutic Use of Neurosteroids for Hypertension - Head, Geoffrey A.; Jackson, Kristy L.; Gueguen, Cindy (Frontiers in Physiology, 2019)
The sympathetic nervous system (SNS) contribution to long term setting of blood pressure (BP) and hence hypertension has been a continuing controversy over many decades. However, the contribution of increased sympathetic vasomotor tone to the heart, kidney and blood vessels has been suggested as a major influence on the development of high BP which affects 30-40% of the population. This is relevant to hypertension associated with chronic stress, being overweight or obese as well to chronic kidney disease. Treatments that have attempted to block the peripheral aspects of the SNS contribution have included surgery to cut the sympathetic nerves as well as agents to block α- and β-adrenoceptors. Other treatments, such as centrally acting drugs like clonidine, rilmenidine or moxonidine, activate receptors within the ventrolateral medulla to reduce the vasomotor tone overall but have side effects that limit their use. None of these treatments target the cause of the enhanced sympathetic tone. Recently we have identified an antihypertensive action of the neurosteroid allopregnanolone in a mouse model of neurogenic hypertension. Allopregnanolone is known to facilitate high affinity extra-synaptic γ-aminobutyric acid A receptors (GABAAR) through allosteric modulation and transcriptional upregulation. The antihypertensive effect was specific for increased expression of δ subunits in the amygdala and hypothalamus. This focussed review examines the possibility that neurosteroids may be a novel therapeutic approach to address the neurogenic contribution to hypertension. We discuss the causes and prevalence of neurogenic hypertension, current therapeutic approaches and the applicability of using neurosteroids as antihypertensive therapy.